A cookbook for the investigation of coordination polymers by transition metal K‐edge XMCD. (2nd June 2021) - N'Diaye, Adama; Bordage, Amélie; Nataf, Lucie; Baudelet, François; Moreno, Thierry; Bleuzen, Anne
Abstract : In order to set up the bases for extracting quantitative information from transition metal K ‐edge X‐ray magnetic circular dichroism (XMCD) signals of coordination polymers, the effects of temperature and magnetic field on these signals are studied. A manual procedure for data treatment is also developed. Key points for transition metal K ‐edge XMCD measurements of coordination polymers on any XMCD‐dedicated beamline are provided. Abstract : In order to disentangle the physical effects at the origin of transition metal K ‐edge X‐ray magnetic circular dichroism (XMCD) in coordination polymers and quantify small structural distortions from the intensity of these signals, a systematic investigation of Prussian blue analogs as model compounds is being conducted. Here the effects of the temperature and of the external magnetic field are tackled; none of these external parameters modify the shape of the XMCD signal but they both critically modify its intensity. The optimized experimental conditions, as well as a reliable and robust normalization procedure, could thus be determined for the study of the intrinsic parameters. Through an extended discussion on measurements on other XMCD‐dedicated beamlines and for other coordination compounds, we finally provide new transition metal K ‐edge XMCD users with useful information to initiate and successfully carry out their projects.